Phylogenetic relation among bovine rabies cases from Minas Gerais and Sao Paulo states, Brazil: a possible common origin (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Bovine rabies transmitted by hematophagous bat Desmodus rotundus has represented a public health challenge and an economical burden to livestock industry of Brazil since 1911, when the first rabies outbreak in this species was officially documented in the south of the country. Several studies revealed temporal and spatial patterns of endemic presentation alternating with epidemic periods. Last registered epizootics occurred between 1997 and 2002, in Sao Paulo affecting bovines and equines near the border of Minas Gerais. The objective of the present research is to perform a phylogenetic analysis of rabies cases in livestock from Minas Gerais municipalities next to Sao Paulo´s epizootic area in the subsequent period (from 2000 to 2009) and try to associate molecular data to geographical and ecological factors. 32 partial DNA sequences were obtained corresponding to rabies external glycoprotein (540 nucleotides of length). To infer genetic relations among virus isolates were performed analysis applying Neighbor- Joining algorithm and Kimura 2 parameter evolution model with 1000 bootstrap repetitions. The proposed phylogeny presented here is in agreement with a previous work (Carnieli, virus research,v 144, p 215, 2009) which prompts the presence of three main sub lineages in the Sao Paulo´s epizootic area, near to the frontier with Minas Gerais: “Old Strain”, RD1 and RD2/RD3. The old Strain is composed by isolates previous to 1998. The strain RD1 is integrated by viruses isolated after 1998 and has a different genetic origin. Lineage RD2/RD3 has subtle genetic difference when compared to RD1 even though they emerged in the same period of time and also have an overlapping pattern of geographic distribution. All samples from Minas Gerais analysed in this research were classified as RD2/RD3. This genetic sub-lineage is located along the border between the two states, mainly over the lowest portions of Serra da Mantiqueira mountain. This genetic sublineage is slightly divergent from rabies isolates from the rest of the country and is possible to differentiate it among rabies viruses from inner municipalities of São Paulo (far from epizootic area), even from older isolates involved in previous epidemic waves as the old and RD1 Strain. Molecular analysis suggests a possible involvement of Artibeus lituratus in the rabies cycle from inner municipalities of São Paulo state. Geographic analysis showed that the cases were mainly distributed in the Mata Altlantica biome and along the rivers: Pardo, Mogi-Guaçu, Piracicaba/Jaguarí and Grande. Molecular analysis suggests that rabies virus circulating in bovines from south of Minas Gerais between 2000 to 2009 is genetically indistinguishable from one of the genetic strains involved in the last epizootics registered in Sao Paulo from 1997 to 2002, called here as RD2/RD3.